2018
DOI: 10.1088/1361-6463/aab1e3
|View full text |Cite
|
Sign up to set email alerts
|

Electron induced ionization of plasma processing gases: C4Fx(x  =  1–8) and the isomers of C4F6and C4F8

Abstract: The total ionization cross section (Qion) for C4Fx (x  =  1–8) fluorocarbons and the isomers of C4F6 and C4F8 molecules are calculated from ionization threshold to 5 keV using the binary-encounter bethe method. The targets are fully optimized using the Hartree–Fock (HF) method and density function theory (DFT) for their minimum energy structure and orbital parameters. The present Qion with HF parameters showed good agreement with the experimental data for 1,3-C4F6, 2-C4F6, 2-C4F8 and 1-C4F8. On the other hand,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…This enables us to find the consistent or recommended sets of data for Q ion . The studies by Gupta et al for the ionization of C 2 F x (x = 1 6), C 3 F x (x = 1 8) [34], and C 4 F x (x = 1 8) [35] neutral and radical species have shown that the use of the DFT (ωB97X) functional may be suitable for fluorocarbon containing species when compared with recent experimental and theoretical data in general. Hence, such functionals can be used for further studies of ionization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This enables us to find the consistent or recommended sets of data for Q ion . The studies by Gupta et al for the ionization of C 2 F x (x = 1 6), C 3 F x (x = 1 8) [34], and C 4 F x (x = 1 8) [35] neutral and radical species have shown that the use of the DFT (ωB97X) functional may be suitable for fluorocarbon containing species when compared with recent experimental and theoretical data in general. Hence, such functionals can be used for further studies of ionization.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, there has been an increase in the research on PFCs for various electron collision processes with the objective of their quantifying cross sections. A complete study of Q ion has been performed for C 2 F x (x = 1 6), C 3 F x (x = 1 8) [34], and C 4 F x (x = 1 8) [35] neutral and radical species using the BEB method. The BEB and CSP-ic methods are briefly described in Section 2.…”
Section: Introductionmentioning
confidence: 99%
“…111) The total ionization cross-sections for perfluorocarbons, such as C 4 F 6 and C 4 F 8 , were calculated using the binary-encounter Bethe method. 112) Various types of analyses of C 4 F 8 plasma were performed, and the dissociation of CF 2 via C 2 F 4 was presumed based on the analysis of the results. 113) Thereafter, the electronic excited states of C 4 F 8 were calculated.…”
Section: 5mentioning
confidence: 99%
“…The ionization collision cross-section can be calculated by the binary-encounter-Bethe (BEB) method [35], Deutsch-Märk (DM) method [36][37][38], and so on [39]. The BEB and DM methods have been improved and successfully used to calculate the ionization collision cross-section for new ecofriendly insulation gases (e.g., C 4 F 8 O, C 4 F 7 N, C 5 F 10 O, C 6 F 12 O [40][41][42][43][44][45][46]). Although the existing methods can provide the cross-sections for calculating α/N, there are still some problems to be solved.…”
Section: Introductionmentioning
confidence: 99%